Existential predication in the languages of the Sudanic belt - Creissels, Denis (AAeO - Afrikanistik-Aegyptologie-Online, 2019)
Among the various types of constructions that may have been referred to as ‘existential’ in the literature, the present article deals with inverse locational predication (abbreviated as ILP), illustrated by English ‘There is a cat in the tree’. Inverse locational predication, like plain (or direct) locational predication, illustrated by English ‘The cat is in the tree’ is characterized by its ability to encode prototypical figure-ground relationships; it differs from plain locational predication in that it encodes the marked perspectivization ‘from ground to figure’. Not all languages have an ILP construction morphologically distinct from plain locational predication, but in many languages that do not have a specialized ILP construction, variation in constituent order is related to variation in perspectivization. However, this is not the case for the languages of the Sudanic belt. A remarkable typological particularity of the languages of this area is that most of them do not have a morphologically distinct ILP construction, and at the same time do not use variation in constituent order to express variation in perspectivization.